PARTISIPASI MASYARAKAT DALAM PENGELOLAAN PARIWISATA TRETES TAMAN TANI DI DESA SAMIRAN SELO BOYOLALI - Nuning Lisdiana; Dwi Kristiani (Universitas Boyolali, 2019)
Involving the community in the process and business development of tourism will be able to foster a sense of ownership and responsibility so that people take care of and preserve the beauty of these attractions. The purpose of this study was to determine the level of community participation in the management of Tretes Taman Tani tourism in Samiran Selo Boyolali Village. This type of research is a qualitative approach with descriptive analytical methods. Data was collected using interview techniques and field observations and documentation, while also utilizing data from books, journals, theses, theses, dissertations, newspapers, the internet, and other relevant materials. The results of his research are the management of the Tretes Taman Tani tourist attraction involving the participation of the village government, landowners and the community in this case involving youth organizations. Community participation is shown by their active participation in managing the parking lot, entrance window, managing the hall and canteen. The role of the government is expected to be a facilitator by giving a greater role and benefit to the community as well as providing an opportunity to channel aspirations or suggestions as well as criticism of the development activities of these attractions. Tourism education needs to be given to the community. Increasing cooperation between tourism institutions, which aims to increase the promotion of Tretes Taman Tani tourism. And people should be more creative in organizing and innovating their products and stall layout arrangements to beautify and provide comfort to the region